Risk factors of oncogenic HPV infection in HIV-positive men with anal condyloma acuminata in Shenzhen, Southeast China: a retrospective cohort study - Liu, Jiaxin; Yang, Rongqing; Zhao, Xiaobao; Chu, Wenzhu; Li, Dapeng; Wang, Fuxiang; Wei, Lanlan (Frontiers in Public Health, 2023)
Background Human immunodeficiency virus (HIV)-positive patients with anal condyloma acuminata (CA) present an increased risk of anal cancer progression associated with oncogenic human papillomavirus (HPV) infection. It is essential to explore determinants of anal infection by oncogenic HPV among HIV-positive patients with CA. Methods A retrospective cohort study was performed in HIV-positive patients with CA between January 2019 to October 2021 in Shenzhen, Southeast China. Exfoliated cells were collected from CA lesions and the anal canal of HPV genotypes detected by fluorescence PCR. Unconditional logistic regression analysis was used to probe associations of independent variables with oncogenic HPV infection. Results Among HIV-positive patients with CA, the most prevalent oncogenic genotypes were HPV52 (29.43%), HPV16 (28.93%), HPV59 (19.20%), and HPV18 (15.96%). Risk of oncogenic HPV infection increased with age at enrollment (COR: 1.04, 95% CI: 1.01–1.07, p = 0.022). In the multivariable analysis, age ≥ 35 years (AOR: 2.56, 95% CI: 1.20–5.70, p = 0.02) and history of syphilis (AOR: 3.46, 95% CI: 1.90–6.79, p < 0.01) were independent risk factors statistically associated with oncogenic HPV infection. History of syphilis (AOR: 1.72, 95% CI: 1.08–2.73, p < 0.02) was also an independent risk factor statistically associated with HPV16 or HPV18 infection. Conclusion In clinical practice, HIV-positive CA patients aged ≥35 years or with a history of syphilis should carry out HR-HPV testing and even anal cancer-related examinations to prevent the occurrence of anal cancer.